Shedding light on taxonomic chaos: Diversity and distribution of South Asian skipper frogs (Anura, Dicroglossidae, Euphlyctis). Issue 1 (31st December 2022) - Dufresnes, Christophe; Mahony, Stephen; Prasad, Vishal Kumar; Kamei, Rachunliu G.; Masroor, Rafaqat; Khan, Muazzam Ali; Al-Johany, Awadh M.; Gautam, Kumudani Bala; Gupta, Sandeep Kumar; Borkin, Leo J.; Melnikov, Daniel A.; Rosanov, Juriy M.; et al.
Abstract : A known haven of amphibian diversity, South Asia is also a hotspot of taxonomic confusions. Vastly distributed from Saudi Arabia to Myanmar, the dicroglossid genus Euphlyctis ("skittering" or "skipper" frogs) is a representative example. Combining phylogenetic analyses with 16S barcoding and genome size variation of 403 frogs from 136 localities, we examined genetic diversity and distributions across the whole range of Euphlyctis, with a particular focus on taxonomic and nomenclatural issues. We recovered two deeply divergent mitochondrial clades totalling ten lineages that we considered as species, and eight could be attributed valid taxonomic names and junior synonyms. The first clade (subgenus Phrynoderma ) is confirmed in South India, Bangladesh and Sri Lanka, and comprises six species: E. karaavali, E. hexadactyla, E. aloysii, E. kerala and two undescribed taxa. Five are endemic to the Western Ghats biodiversity hotspot and four of them form the E. aloysii species complex. The second clade (subgenus Euphlyctis ) extends across South Asia and neighbouring regions, and comprises four species: E. ehrenbergii, E. jaladhara, and two widespread lineages erroneously called " E. mudigere " and " E. kalasgramensis " in recent literature, while their oldest valid names appear to be E. cyanophlyctis and E. adolfi, respectively. Additional analyses on this pair of taxa highlighted strong phenotypic resemblance, notable intraspecific phylogeographic structure, and an extensive contact zone along the southern slopes of the Himalaya, with putative signs of genetic introgression. Through an independent investigation of the historical literature, we identified overlooked issues and misconceptions regarding the status of many old and recent taxa, and proposed solutions, such as transferring " E. ghoshi " to the genus Limnonectes . Our study illustrates how range-wide genetic barcoding can clarify taxonomic confusions, and we call to solve remaining issues prior to the description of new taxa.